THE POWER OF SHARIA FINANCIAL TECHNOLOGY REGULATION IN INDONESIA - Dian Febriyani (Jurnal Ekonomi, 2022)
In today's digital era, all activities using digital systems provide convenience and speed in carrying out all the activities needed, one of which is conducting financial transactions. Financial technology provides digital financial transaction services with various convenient features to make the required financial transactions. The presence of fintech certainly changes people's behavior in financial transactions with the conveniences offered by fintech services. Islamic financial institutions also follow the development of digital services and meet the needs of the public in conducting sharia-based digital financial transactions. With this change in digital financial transaction patterns, it is necessary to have a regulation that regulates and supervises the running of sharia-based fintech business practices in Indonesia. This study aims to analyze the basics of sharia fintech business regulations in Indonesia and explain the impact of these regulations on the development of sharia fintech in Indonesia. The study used normative juridical methods. The results showed that in Indonesia, the legal basis for the running of sharia fintech was POJK No. 77/POJK.01/2016. OJK changed the regulation with the issuance of POJK No. 10/POJK.05/2022, which specifically regulates the running of sharia fintech in Indonesia. This can provide regulatory strength to the running of sharia fintech services.